βIII-Tubulin Gene Regulation in Health and Disease - Duly, Alastair M. P.; Kao, Felicity C. L.; Teo, Wee Siang; Kavallaris, Maria (Frontiers in Cell and Developmental Biology, 2022)
Microtubule proteins form a dynamic component of the cytoskeleton, and play key roles in cellular processes, such as vesicular transport, cell motility and mitosis. Expression of microtubule proteins are often dysregulated in cancer. In particular, the microtubule protein βIII-tubulin, encoded by the TUBB3 gene is aberrantly expressed in a range of epithelial tumours and is associated with drug resistance and aggressive disease. In normal cells, TUBB3 expression is tightly restricted, and is found almost exclusively in neuronal and testicular tissues. Understanding the mechanisms that control TUBB3 expression, both in cancer, mature and developing tissues will help to unravel the basic biology of the protein, its role in cancer, and may ultimately lead to the development of new therapeutic approaches to target this protein. This review is devoted to the transcriptional and posttranscriptional regulation of TUBB3 in normal and cancerous tissue.